Flexible All‐Inorganic Room‐Temperature Chemiresistors Based on Fibrous Ceramic Substrate and Visible‐Light‐Powered Semiconductor Sensing Layer. Issue 23 (20th October 2021) - Han, Chaohan; Li, Xiaowei; Liu, Yu; Tang, Yujing; Liu, Mingzhuang; Li, Xinghua; Shao, Changlu; Ma, Jiangang; Liu, Yichun
Abstract: As the most extensively used gas‐sensing devices, inorganic semiconductor chemiresistors are facing great challenges in realizing mechanical flexibility and room‐temperature gas detection for developing next‐generation wearable sensing devices. Herein, for the first time, flexible all‐inorganic yttria‐stabilized zirconia (YSZ)/In2 O3 /graphitic carbon nitride (g‐C3 N4 ) (ZIC) gas sensor is designed by employing YSZ nanofibers as substrate, and ultrathin In2 O3 /g‐C3 N4 heterostructures as active sensing layer. The YSZ substrate possesses small nanofiber diameter (310 nm), ultrafine grain size (23.9 nm), and abundant dangling bonds, endowing it with striking mechanical flexibility and strong adhesion with In2 O3 /g‐C3 N4 sensing layer. Meanwhile, the ultrathin thickness (≈7 nm) of In2 O3 /g‐C3 N4 ensures that the inorganic sensing layer has tiny linear strain along with the deformation of flexible YSZ substrate, thereby enabling unusual bending capacity. To address the operating temperature issue, the gas sensor is operated by using a visible‐light‐powered strategy. Under visible‐light illumination, the flexible ZIC sensor exhibits a perfectly reversible response/recovery dynamic process and ultralow detection limit of 50 ppb to toxic nitrogen dioxide at room temperature. This work not only provides an insight into the mechanical flexibility of inorganic materials, but also offers a valuable reference for developing other flexible inorganic‐semiconductor‐based room‐temperature gas sensors. Abstract : A unique flexible all‐inorganic yttria‐stabilized zirconia (YSZ)/In2 O3 /graphitic carbon nitride (g‐C3 N4 ) gas sensor is developed by employing YSZ nanofibers as substrate, and ultrathin In2 O3 /g‐C3 N4 heterostructures as active sensing layer. Under visible‐light illumination, the flexible sensor exhibits perfectly reversible response/recovery dynamic process to toxic NO2 under extreme bending state at room temperature.